Kampinos National Park Activities in Relation to the Encyclical Laudato Si’ - Mickiewicz, Małgorzata (Studia Ecologiae et Bioethicae, 2017)
National parks play a very significant role in the nature conservation system in Poland. The Kampinos National Park situated in the immediate vicinity of Warsaw is one of the most valuable protected areas. It stands out for its natural, cultural, social, and scientific values. It is important for biodiversity conservation, scientific research, and ecological education. Thanks to its attractiveness, it is often visited by tourists. By performing its formal duties, the Park fulfills Pope Francis’ premise contained in the encyclical Laudato Si’. By preserving wild nature and cultural heritage for future generations, it creates conditions to explore natural, social, and economic phenomena. At the same time, it offers excellent conditions for recreation and tourism. A wide offer of educational activities is provided for groups of people of different ages and professions. This is how the Park implements Pope Francis’ idea of changing the ecological culture and understanding the responsibility for the natural condition of the environment by all members of the society.